The Importance of Basic Health in Early Childhood:An Observational Study at UPTD Puskesmas Cempae, Parepare City - Maswati; Wahyuni; Hasma; Fatmah; Basirah; Gusriani; Nurul Hikmah; Rahmadana; Sitti Hadijah (CV Edujavare Publishing, 2026)
Basic health in early childhood constitutes a critical foundation for optimal growth and development that determines the quality of human resources in the future. Early childhood (0–6 years), known as the golden age, is characterized by rapid brain development reaching approximately 90% of adult brain capacity. This study aimed to examine the implementation of basic health programs for early childhood, including Clean and Healthy Living Behavior (PHBS), balanced nutrition fulfillment, and immunization at UPTD Puskesmas Cempae, Parepare City. The study used a descriptive qualitative approach through direct observation and documentation at the Maternal and Child Health (KIA) unit, conducted from April 20–22, 2026. Results indicated that the PHBS program has been running satisfactorily, with positive indicators in handwashing habits and school environmental hygiene, although health center guidance remains limited to approximately once per year. In the nutritional aspect, a stunting prevalence of 2% was found among 730 registered toddlers. Complete basic immunization coverage remained below 90%, influenced by parental fear of side effects, misinformation, and socioeconomic factors. The success of basic health programs for early childhood requires active synergy among health workers, families, schools, and communities as an integrated and sustainable health ecosystem.